Does living alone exacerbate depression in older adults? - Wang, Haolin; Sun, Bing (Frontiers in Psychology, 2025)
IntroductionLiving alone, which has become increasingly common in China, weakens the emotional connections between parents and children—fundamental family functions in Confucianism. This trend has raised concerns regarding depression among older adults living alone. Numerous researchers have evaluated the influence of living alone on depression among older adults in different cultures. However, the consensus has yet to be reached.MethodsThis study adopted a fixed effects model to analyze three sets of data from the China Health and Retirement Longitudinal Study based on different family cultures reflected by living arrangements.ResultsLiving alone reduced depression among older adults by 0.267 (CES-D, 10–40). The effects of living alone on depression among older adults predominantly originate from living close to their children. This lifestyle effectively balances the need for individual independence and the demand for maintaining tight family relationships and reconciles intergenerational family conflict. Differences between rural and urban areas were also identified. This search indicated that living alone improved depression in rural older adults; however, no significant effects were found for urban older adults.DiscussionAs living close to their children is conducive to improving depression among older adults, policymakers are advised to focus on local employment. Special emphasis should be placed on incentivizing migrant workers to return to their rural hometowns for entrepreneurship or employment.